Pola Makan Dan Aktivitas Fisik Pada Pasien Diabetes Mellitus Tipe 2 Di Rumah Sakit Pancaran Kasih Manado - I Made Djendra; Muksin Made Pasambuna; Siani Pintan (Jurnal GIZIDO, 2019)
The purpose of this study was to determine the relationship between diet and physical activity on blood sugar levels of Type 2 Diabetes Mellitus patients at Pancaran Kasih Hospital in Manado City and the results of this study can be used as input material for patients to be able to maintain their diet and regulate physical activity to control blood sugar levels remain at normal limits. Diabetes mellitus is a chronic condition where the body cannot or does not produce insulin optimally. The study design used was a type of observational study with a cross sectional approach to determine the relationship between risk factors and disease. In this study used 2 independent variables, namely diet and physical activity and the dependent variable Diabetes Mellitus. The method of taking samples is using purposive sampling in accordance with the proposed inclusion and exclusion criteria. The samples needed in this study were 41 people determined by the Slovin formula. From the results of this study note that eating patterns have a value of p = 0.00, p <0.05 which means there is a significant relationship with eating patterns with blood sugar levels of Type 2 Diabetes Mellitus patients. Results of physical activity p = 0.03, p < 0.05 which means there is a significant relationship between physical activity and blood sugar levels in Type 2 Diabetes Mellitus patients at Pancaran Kasih Hospital in Manado City.